Las sagradas imágenes en los sínodos y concilios americanos anteriores a la vigésimo quinta sesión del concilio de Trento - Guzmán Schiappacasse, Fernando (Hispania sacra, 2022)
The American synods and councils before the formulation of the Tridentine decree of 1563, on the invocation and veneration of the relics of saints and sacred images, established criteria and guidelines for religious painting and sculpture. The bishops and priests who participated in these discussions kept in mind the pastoral practice, the previous theological discourse, as well as what was resolved by Spanish synods and councils. The present paper aims to characterize these American ecclesiastical documents and to identify the sources that are feeding their formulation. The decisive factors of this genealogy of American thought on sacred images would be the doctrine elaborated from the First Fathers to the European ecclesiastical documents of the early sixteenth century, the tension that the issue of sacred images caused between the Spanish population of Jews and Muslim converts, as well as the practices that were implemented since 1492 to Christianize the Muslim population of Granada.